A comparative study of device driver APIs towards a uniform linux approach - Ouaiss, Iyad (2017)
Linux Application Program Interfaces (APIs) lack stability and standardization. There is a need for a standard API for Linux device drivers that allow backward compatibility while easing the development of new drivers. The advantage of standardizing the API is to make the kernel core more robust and the development of new drivers easier; however the main challenge is performance-based. This work starts by carefully studying the available APIs for Linux as well as for other platforms. Current solutions studied include the Uniform Driver Interface (UDI), the Intelligent I/O architecture (I2O), WinDriver, and APIs implemented in Solaris, and Windows XP. By listing the strengths and weaknesses of available APIs, a proposal for a new Linux API is constructed that defines a standard interface, provides backward compatibility, ensures kernel security, and handles errors, uniform block sizes, buffering, etc.